Structural, morphological, optical, and thermal properties of electrospun PbS/PVP-PEO nanofibers. Issue 6 (15th March 2023) - Sharma, Deep; Patel, Nidhi; Panjabi, Sanjay; Patel, Vaibhav
Abstract: This study describes the preparation and characterization of PVP-PEO nanofibers filled with PbS nanoparticles. The effect of polymer concentrations, surface morphology, and diameter distribution studies of the nanofibers was evaluated by Scanning Electron Microscopy (SEM). The SEM images revealed that smooth and homogeneous nanofibers could be achieved at 12% PVP-PEO (50:50 wt%) concentration. The XRD and TEM analysis confirmed the formation of PbS nanoparticles in the PVP-PEO blend matrix, which also revealed the high crystalline behaviour of the PbS nanoparticles. The XRD data showed that the intensity and average crystallite size increase with PbS concentration. The FTIR and TGA studies revealed the interaction between PbS nanoparticles and the PVP-PEO blend matrix. UV–Vis diffuse reflectance studies have shown that the reflectance onset shifted toward a blue shift than bulk PbS. The optical bandgap determined using the Kubelka-Munk function lies 1.08–1.56 eV range by varying PbS concentration.